Advantages of Outpatient Treatment with Long‐Acting Lipoglycopeptides for Serious Gram‐Positive Infections: A Review. Issue 5 (23rd April 2020) - Krsak, Martin; Morrisette, Taylor; Miller, Matthew; Molina, Kyle; Huang, Misha; Damioli, Laura; Pisney, Larissa; Wong, Megan; Poeschla, Eric
Abstract : Treatment of serious gram‐positive infections presents multiple challenges. Treatment often results in prolonged hospitalization for administration of intravenous antimicrobials and presents an inefficient use of hospital resources. Prolonged hospitalization is typically also unfavorable to patient preferences and potentially subjects patients to additional health care‐associated complications. Current strategies of transition to outpatient settings—outpatient parenteral antimicrobial therapy and use of oral antibiotics—often do not adequately serve vulnerable populations for whom there is often no alternative to inpatient therapy. Specifically, people who use drugs, those who cannot reliably adhere to unsupervised treatment (poor mental or physical health), people with complicating life circumstances (e.g., homelessness, incarceration, rural location), and those with inadequate health insurance remain hospitalized for weeks longer than persons without such conditions. We suspected that long‐acting lipoglycopeptides (laLGP), such as dalbavancin and oritavancin, may be useful in patient transitions to outpatient settings. Thus, we conducted a search of the peer‐reviewed literature using the PubMed, Google Scholar, and MEDLINE databases. Based on accumulating literature, it appears that laLGPs offer a reliable alternative therapeutic strategy that addresses many of the personal and systemic barriers to the traditional transitioning approaches. Current evidence also suggests that these agents may be cost‐effective from patient, payer, and hospital perspectives. Barriers to broader use of laLGPs include, among others, a relative lack of prospective data regarding efficacy in serious infections, a narrow United States Food and Drug Administration–approved indication restricted to only acute bacterial skin and skin structure infections, and lack of reimbursement infrastructure for inpatient settings.